2015
DOI: 10.1128/aem.00780-15
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota at Multiple Body Sites during Pregnancy in a Rural Tanzanian Population and Effects of Moringa-Supplemented Probiotic Yogurt

Abstract: The nutritional status of pregnant women is vital for healthy outcomes and is a concern for a large proportion of the world's population. The role of the microbiota in pregnancy and nutrition is a promising new area of study with potential health ramifications. In many African countries, maternal and infant death and morbidity are associated with malnutrition. Here, we assess the influence of probiotic yogurt containing Lactobacillus rhamnosus GR-1, supplemented with Moringa plant as a source of micronutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 44 publications
6
109
1
Order By: Relevance
“…In contrast, DiGulio et al collected rectal swabs weekly from the end of the first trimester to delivery in 40 US women (11 of which delivered preterm) and observed only marginal decreases in alpha diversity (Shannon diversity index) over the gestational period (p = 0.05), and no changes to microbial beta diversity nor shifts in relative abundance of taxa [26]. Likewise, a study of 56 Tanzanian women (26 of whom received probiotic supplementation), in which monthly stools were collected from 12 to 24 weeks of pregnancy to parturition, found no significant changes in the gut microbiota beta diversity over the course of pregnancy; in this study, changes in alpha diversity or relative abundance of specific taxa with pregnancy were not reported [27]. The divergent study results may be attributable to differences in the following: ( i ) the frequency and method of sampling, ( ii ) the hypervariable regions amplified (V1/V2 vs. V3–V5 vs. V4 in the three studies, respectively), or ( iii ) the size and composition of the cohorts studied.…”
Section: Pregnancy and The Microbiomementioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, DiGulio et al collected rectal swabs weekly from the end of the first trimester to delivery in 40 US women (11 of which delivered preterm) and observed only marginal decreases in alpha diversity (Shannon diversity index) over the gestational period (p = 0.05), and no changes to microbial beta diversity nor shifts in relative abundance of taxa [26]. Likewise, a study of 56 Tanzanian women (26 of whom received probiotic supplementation), in which monthly stools were collected from 12 to 24 weeks of pregnancy to parturition, found no significant changes in the gut microbiota beta diversity over the course of pregnancy; in this study, changes in alpha diversity or relative abundance of specific taxa with pregnancy were not reported [27]. The divergent study results may be attributable to differences in the following: ( i ) the frequency and method of sampling, ( ii ) the hypervariable regions amplified (V1/V2 vs. V3–V5 vs. V4 in the three studies, respectively), or ( iii ) the size and composition of the cohorts studied.…”
Section: Pregnancy and The Microbiomementioning
confidence: 59%
“…Three of the four also reported movement between distinct vaginal community state types [26, 28, 30]. While there has been speculation that the vaginal microbiome is colonized by the maternal gut microbiome (via the rectum) toward the end of pregnancy [31], there is limited empirical support for this hypothesis [27]. …”
Section: Pregnancy and The Microbiomementioning
confidence: 99%
“…In contrast to the structural stability of the vaginal microbiota during pregnancy, studies of women in the USA, Europe, Africa, and Asia have shown that upon delivery, the vaginal microbiota commonly undergoes an abrupt and striking alteration in its taxonomic composition 14,1719 . This alteration is characterized by significantly increased alpha-diversity and is driven by a decrease in the abundance of Lactobacillus spp.…”
Section: Maternal Microbial Ecologymentioning
confidence: 99%
“…This change correlated with compositional shifts in the microbiota 21 . However, studies of women residing in the USA 14 and in Tanzania 17 , conducted at higher temporal resolution, found that their fecal microbiota manifested compositional stability throughout pregnancy (as measured by trends of alpha diversity, week-to-week variation within subjects, and beta diversity across gestational time), though the reasons for these divergent findings are unclear. Maternal microbiota and diet have the potential to influence both fetal and maternal epigenomes as well, although a discussion of this topic is beyond the scope of this Perspective .…”
Section: Maternal Microbial Ecologymentioning
confidence: 99%
See 1 more Smart Citation